2021
DOI: 10.1042/bsr20203584
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia at admission is a strong predictor of mortality and severe/critical complications in COVID-19 patients: a meta-analysis

Abstract: Background: Hyperglycaemia at admission has been demonstrated to exacerbate the outcomes of coronavirus disease 2019 (COVID-19) but a meta-analysis is lacking to further confirm this hypothesis. The purpose of this meta-analysis was to summarize the evidence on the association between hyperglycaemia at admission and the development of COVID-19. Method: Four databases namely, PubMed, Web of Science, Embase and Cochrane Library, were screened for eligible studies. STATA software was utilized to pool data for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 40 publications
5
26
0
1
Order By: Relevance
“…A growing number of observational studies have shown that hyperglycemia is a strong predictor of morbidity and mortality in hospitalized and critically ill COVID-19 patients, independent of pre-existing diabetes status [ 11 , 12 , 13 ]. However, it is still unclear how the combination of underlying T2D and the presence of hyperglycemia at the time of hospital admission is associated with the inflammatory burden and outcomes of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of observational studies have shown that hyperglycemia is a strong predictor of morbidity and mortality in hospitalized and critically ill COVID-19 patients, independent of pre-existing diabetes status [ 11 , 12 , 13 ]. However, it is still unclear how the combination of underlying T2D and the presence of hyperglycemia at the time of hospital admission is associated with the inflammatory burden and outcomes of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…[2] As majority of cases develop mild symptoms or are asymptomatic, [3,4] many have identified several risk factors associated with poor outcomes to better triage and allocate scarce health resources. [5][6][7][8][9][10][11] Recently, multiple observational studies reported the prevalence of electrolyte disorders amongst COVID-19 patients and have suggested its association with COVID-19 severity. [12,13] For example, Tzoulis et al found that adults with COVID-19 and dysnatremia was associated with a higher risk for mechanical ventilation and mortality in adults.…”
Section: Resultsmentioning
confidence: 99%
“…In non critically ill patients, elevated glucose values were associated with a worse prognosis [14][15][16][17][18][19][20][21][22], but heterogeneity in study design can be detected in these investigations concerning study population (diabetics versus non diabetics) and blood glucose measurements (admission, fasting, in hospital glucose values). In a two-center retrospective investigation [17] (605 COVID patents without previous diagnosis of diabetes) fasting blood glucose (FBG 7.0 mmol/l) at admission was an independent predictor for 28-day mortality .…”
Section: Discussionmentioning
confidence: 99%